Optimum dose of nitrogen and potassium for ginger in Wynad, Kerala - Satheesan, K Kumaran, T Pradeepkumar, P Mayadevi, K C Aipe, T P Manomohandas, M P Giridharan, K N (Journal of Spices and Aromatic Crops, 2001)
Study on nutrient requirement of ginger in Wynad, Kerala showed the positive effect of higher, doses of Nand K on the yield. Among the 16 levels of Nand K, 3 combinations viz., 150 kg N, 50 kg K; 150 kg N, 100 kg K and 75 kg N, 150 kg K ha-1 were found to be significantly superior with respect to yield. Among the vegetative characters, plant height was found to be significantly influenced by nitrogen. The optimum dose of Nand K derived from the quadratic equation was 144 kg and 109 kg ha-1 respectively.